Behavioral effects of the neurotoxin ß-N-methylamino-L-alanine on the mangrove rivulus (Kryptolebias marmoratus) larvae - Alessandra Carion; Julie Hétru; Angèle Markey; Victoria Suarez-Ulloa; Silvestre Frédéric (MDPI AG, 2018)
Mangrove rivulus, Kryptolebias marmoratus, is a hermaphrodite fish capable of self-fertilization. This particularity allows to naturally produce highly homozygous and isogenic individuals. Despite the low genetic diversity, rivulus can live in extremely variable environments and adjust its phenotype accordingly. This species represents a unique opportunity to clearly distinguish the genetic and non-genetic factors implicated in adaptation and evolution, such as epigenetic mechanisms. It is thus a great model in aquatic ecotoxicology to investigate the effects of xenobiotics on the epigenome, and their potential long-term impacts. In the present study, we used the mangrove rivulus to investigate the effects of the neurotoxin ß-N-methylamino-L-alanine (BMAA) on larvae behaviors after 7 days exposure to two sub-lethal concentrations. Results show that BMAA can affect the maximal speed and prey capture (trials and failures), suggesting potential impacts on the organism's fitness.